Annex of the Faculty of Electronics in Nis - Stanimirović, Mirko; Kondić, Slaviša; Tanić, Milan; Nikolić, Vojislav (Arhitektura i urbanizam, 2022)
Along with the architecture, this presentation also discusses the development of the study program at the Faculty of Electronics in Niš, which directly influenced the design of its new annex. With the idea of enabling a more thorough education and a faster interconnection between science and entrepreneurship, the Ministry of Education, Science and Technological Development of the Republic of Serbia invested in the construction of the Multi-Purpose Lamella at the Faculty of Electronics, University of Niš. The project was completed by the Teking Architecture Studio from Niš. The lamella is an extension of the existing building of the Faculty of Electronics, forming a coherent whole with it. The design concept of the building was developed by integrating a number of key influential determinants (program, place and time of construction), and it reflects and emphasizes the architecture of the original structure.